Inducing behavioral change: an experiment. Issue 4 (1st October 2020) - Moreno-Jaimes, Carlos; Meza, Oliver
Abstract: To what extent can public policy affect the behavior of target populations without making far-reaching institutional or organizational changes? We investigate the efficacy of a policy instrument designed to increase people's adherence to physical exercise. Based on social norms theory, we developed a communication strategy consisting in the weekly delivery of two types of messages to people's cell-phones: one that informed them about their previous attendance to the gym, and another that encouraged them to exercise through a motivational phrase and image. We conducted a field experiment to test the efficacy of such strategy. Our results demonstrate that, for people who already developed the habit of exercising, descriptive messages did not induce them to improve their attendance to the gym given that they deemed they had exceeded their weekly exercise quota. On the contrary, motivational messages did improve attendance. Our research emphasizes that non-rational motivations can have important consequences on inducing healthy habits. It also claims that interventions such as the one we carried out is of practical importance for policy designers and implementation managers who, lacking the formal power to create radical changes, can nevertheless influence the behavior of target populations.